WOMEN POWER TO END THE OPPRESSIONS OF PATRIARCHY IN SUSAN GLASPELL’S PLAY ‘TRIFLES’ - Asianti, Dwi Anggara (Universitas Negeri Semarang, 2012)
In patriarchy society, women do not have other choice but obey all rules set by men. As a result, womenÃ¢â‚¬â„¢s life marginalized and gap between womenÃ¢â‚¬â„¢s role and menÃ¢â‚¬â„¢s occurred.The same condition and situation faced by a woman, as the main character, in Susan GlaspellÃ¢â‚¬â„¢sÃ‚Â entitled Ã¢â‚¬ËœTriflesÃ¢â‚¬â„¢. This paper would like to identify the patriarchy oppressions and analyze action as the reflection ofÃ‚Â womenÃ¢â‚¬â„¢s power to end the oppressions of patriarchy. The women power, subtle and indirect, that may the women themselves never realize they have it